Halal Label, BPOM Certification, and Cosmetic Purchase Decisions: The Moderating Role of Price Among Islamic Economics and Business Students - Alik, Samsidar; Mas, Nur Amal; Imam, Muh. Abdi (Institut Agama Islam Negeri Palopo, 2025)
This thesis discusses the Influence of Halal Labels and BPOM on Purchase Decisions with Price as a Moderation Variable of the FEBI IAIN Palopo Student Study.This study aims to analyze the variables of halal labels and BPOM on cosmetic purchase decisions in FEBI IAIN Palopo students. To analyze halal label variables and prices on the decision to purchase cosmetics of FEBI IAIN Palopo students. To analyze the influence of BPOM and price on cosmetic purchase decisions and to analyze halal labels, BPOM, and prices on cosmetic purchase decisions of FEBI IAIN Palopo students. The method used is a quantitative research method that uses data in the form of numbers as a tool to determine information about what you want to know. The data source used is primary data through questionnaires. The population was 2,983 people using the slovin formula, the number of samples used was 97 respondents. As well as using purposive sampling. The methods used to test the hypothesis are classical assumption test, hypothesis test, multiple linear regression, and moderated Regression Analysis (MRA). The analysis tool in this study uses the help of SPSS Version 20. The results of this study show that halal label variables have a positive and significant effect on purchase decisions. BPOM variables have a positive and significant effect on purchase decisions. So that the halal label and BPOM have a simultaneous effect that directly affects the purchase decision by 73.4% while the remaining 26.6% is influenced by other variables outside the model. The results of the study using moderation variables show that the price variable cannot moderate the halal label variable on the purchase decision. The price variable also cannot moderate the BPOM variable on the purchase decision. So that the halal label, and BPOM cannot influence the purchase decision by 75.8% after the interaction of price variables as a moderation variable. Keywords: BPOM, Price, Purchasing Decision, and Halal Label.